Reading of the Mitsuda test: comparison between diameter and total area by means of a computerized method - Edilamar Silva de Alecrim; Ana Thereza Chaves; Luiz Alberto Bomjardim Pôrto; Maria Aparecida de Faria Grossi; Sandra Lyon; Manoel Otávio da Costa Rocha (Revista do Instituto de Medicina Tropical de São Paulo, 2019)
ABSTRACT The Mitsuda test is a skin test based on the individual’s immune response through late and highly specific hypersensitivity reaction to the Mycobacterium leprae bacillus. A negative reaction identifies individuals who present a higher risk of becoming ill if exposed to M. leprae and, if they become ill, to develop the virchowian form of disease. The Mitsuda test reading is performed by means of a millimeter ruler. The dermatoscopy is a method that has not been used in the evaluation of cutaneous tests, although its use has increased in several areas. The study aimed to compare the results between the standardized reading and the total area of the Mitsuda test obtained by a computerized method which was structured by the association of digital dermatoscopy, the Dermatology Web system and the Image Tool 3.0 software. Data collection was performed at the Dermatology Outpatient Clinic of the Eduardo de Menezes Hospital, in Belo Horizonte, from November 2015 to August 2016. The sample consisted of 100 leprosy domiciliary contacts. There was an excellent agreement between the Mitsuda test (diameter and area), with a coefficient greater than 80%, and an excellent correlation with the Spearman’s correlation coefficient (0.936). The intraclass correlation coefficient indicated a low (0.219) but significant agreement between the two measurements. In conclusion, there is a significant correlation between the standardized reading and the total area of the Mitsuda test. Digital dermoscopy can be an alternative instrument of evaluation, allowing the computerization and recording of the Mitsuda test.